Kajian Pemanfaatan Tailing Pengolahan Emas Untuk Pembuatan Batako Sebagai Aplikasi Zero Waste Material Di PT Global Minerallium Corporindo Kecamatan Batu Sopang Provinsi Kalimantan Timur - Mu’adz Ma’ruf Fakhruddin; Dyah Probowati (Jurnal Penelitian Rumpun Ilmu Teknik, 2024)
This research aims to reuse solid tailings from gold processing from PT Global Minerallium Corporindo into a mixture for making concrete bricks as a form of the Zero Waste movement where no material is thrown away. This research was conducted by mixing tailings with a ratio of 10%, 20% and 30% in the dough for making bricks. After the bricks are formed, the composition and pH of the solid tailings will be analyzed, the value of compressive strength, and the percentage of water absorption in the bricks. The composition test is carried out using portable XRF which will be fired directly at the tailings. The pH test is carried out using a soil pH test by inserting a probe into solid tailings that has been moistened with a little water. While the compressive strength test and percent water absorption test will be carried out in accordance with SNI 03-0349-1989. From the results obtained, the highest compressive strength value was obtained in a 10% tailings mixture with a value of 91,10 kgF/cm2. Whereas the lowest percentage of water absorption was obtained in a 30% tailings mixture with a value of 3.88%. However, overall the 10% brick mixture is the optimal mixture for forming bricks because it meets the quality standards for bricks II, III, and IV SNI 03-0349-1989.